Cocoa’s Residual Honey: Physicochemical Characterization and Potential as a Fermentative Substrate by Saccharomyces cerevisiae AWRI726 - Paula Bacelar Leite; Wanderson Mariano Machado; Alaíse Gil Guimarães; Giovani Brandão Mafra de Carvalho; Karina Teixeira Magalhães-Guedes; Janice Izabel Druzian (The Scientific World Journal)
This study aims to characterize the physicochemical properties of cocoa’s residual honey and evaluate its fermentative capacity as a substrate, using Saccharomyces cerevisiae AWRI726 as the starter culture for alcoholic fermentation. The research hypothesis was that cocoa’s residual honey can be used for the production of fermented beverages. Cocoa’s honey has 14.14 g.100 mL−1 of dry material, containing 11.80 g.100 mL−1 of carbohydrates and 1.20% crude protein, in addition to other minor components, such as pectin, lipids, and Fe, Mn, Na, and Zn, with a carbon-to-nitrogen (C/N) ratio (9.8) most suitable for fermentation. Fermentation at 20°C for 240 hours produced a liquid with 16% v/v ethanol (14 g.L−1 in 144 h). However, 24 hours of fermentation produced the maximum ethanol yield (0.373 g.g−1) and volumetric productivity (0.168 g.L−1.h−1), which were associated with a significant increase in the specific cell growth rate. Saccharomyces cerevisiae AWR1726 performed satisfactorily in the alcoholic fermentation of cocoa’s residual honey, similar to that observed in other fruit beverages, thus suggesting the suitability of cocoa’s residual honey for future commercial applications.